Явище електроконтактної пам'яті термоантрациту - Лакомський, В.Й. (Видавничий дім "Академперіодика" НАН України, 2008)
Electrode thermoanthracite is the main raw material in the carbon electrode production. The study of electrocontact properties of thermoanthracite reveals, for the first time, its new physical phenomenon ─ the electrocontact memory.